Italian Ryegrass Control Using a Capsule Suspension Formulation of S-metolachlor in Fenclorim-treated wheat - Jason K. Norsworthy; Samuel C. Noe; Tristen H. Avent; Thomas R. Butts; Trent L. Roberts (Weed Technology, 2025)
Italian ryegrass control is one of the most significant limitations in wheat production in the United States today. Resistance to Herbicide Resistance Action Committee (HRAC)/Weed Science Society of America (WSSA) Groups 1, 2, and 9 in Arkansas have further complicated postemergence control, whereas residual herbicides still show effective weed control. One problem is the potential of HRAC/WSSA Group 15 herbicides to injure wheat when applied preemergence, indicating the need for a herbicide safener. A series of experiments were conducted in Fayetteville, AR, to evaluate crop tolerance and Italian ryegrass control using a capsule suspension (CS) formulation of S-metolachlor in conjunction with fenclorim-treated wheat. Experiments were conducted as a two-factor factorial with S-metolachlor applied at three rates (0.37, 0.74, and 1.12 kg ai ha–1) and a microencapsulated formulation of acetochlor at 1.05 kg ai ha–1, and three rates of a fenclorim seed treatment at 0, 0.5, and 2.0 g ai kg–1 of seed. Separate experiments utilized either a preemergence (PRE) or a delayed-preemergence (DPRE) application timing. In both experiments, S-metolachlor at 0.74 and 1.12 kg ai ha–1 provided 77% to 96% control of Italian ryegrass by preharvest, whereas acetochlor only provided 49% to 72% control. Visible wheat injury from PRE applications ranged from 7% to 49% for all treatments 21 d after treatment (DAT), with a reduction in injury when fenclorim-treated wheat was used for both the 0.74 and 1.12 kg ai ha–1 rate of S-metolachlor. In the DPRE experiments, wheat injury ranged from 5% to 16% 21 DAT with no noticeable safening from the presence of fenclorim at any herbicide rate. The results of these experiments indicate that a DPRE application using a CS formulation of S-metolachlor would be more favorable for producers to mitigate the potential for injury to wheat while providing Italian ryegrass control. Additionally, at the DPRE application timing, fenclorim is unnecessary for S-metolachlor to be safely applied at the rates evaluated.